Determination of frequency of thalassaemia trait in a rural tertiary care hospital of India by using various red cell indices as screening tool. - Pethe, Neeraja; Munemane, Anil; Dongre, Suryakant (Annals of Pathology and Laboratory Medicine, 2015)
Background:Thalassemias are among the most common genetic disorders in humans. The blood picture of thalassaemia trait and iron deficiency anaemia is that of microcytic hypochromic anaemia and hence it is of utmost importance to differentiate between these two conditions. The patients with beta thalassemia trait who are treated under the mistaken diagnosis of iron deficiency may develop siderosis leading to cardiac arrhythmias, congestive heart failure and ultimately death. Thalassemia trait being common in this particular area, the present study was conducted in a rural tertiary care hospital of Western Maharashtra, India with an aim to determine the frequency of thalssemia trait and to differentiate thalassemia trait from iron deficiency anaemia. Methods: Blood sample of the patients was collected in K3 EDTA tubes and the various parameters were checked by an automated cell counter. By using these parameters, values of the 4 indices were calculated. These included the England and Fraser’s index, the Mentzer’s index, Red cell distribution width and RBC count. Results: During the study period out of 3362 patients who underwent haematological investigations, 14.87% had microcytic hypochromic anaemia. Depending on the positivity of the indices, probable numbers of cases of thalassaemia trait were calculated.6.2 % cases are most probably of thalassaemia trait by using all the four indices. Conclusion: Red cell distribution width, RBC count, England and Fraser’s index, and Mentzer index can be used as initial discrimination between the iron deficiency anaemia from thalassemia trait. For confirmation of thalassemia trait HbA2 estimation is essential.